2019
DOI: 10.1038/s41598-019-43638-0
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells of Systemic Sclerosis patients, derived from different sources, show a profibrotic microRNA profiling

Abstract: Systemic Sclerosis (SSc) is a disease with limited therapeutic possibilities. Mesenchymal stem cells (MSCs)-therapy could be a promising therapeutic option, however the ideal MSCs source has not yet been found. To address this problem, we perform comparison between bone marrow (BM)-MSCs and adipose (A)-MSCs, by the miRs expression profile, to identify the gene modulation in these two MSCs source. MicroRNAs (miRs) are RNAs sequences, regulating gene expression and MSCs, derived from different tissues, may diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
(86 reference statements)
2
12
1
Order By: Relevance
“…5). Similarly to Di Benedetto et al., our results also demonstrated upregulated expression of miRNA‐10b in SSc [33]. Out of five selected miRNAs, the same expression pattern between miRNA‐seq and qPCR analysis was confirmed only in miRNA‐26a‐2‐3p and miRNA‐485‐3p.…”
Section: Discussionsupporting
confidence: 87%
“…5). Similarly to Di Benedetto et al., our results also demonstrated upregulated expression of miRNA‐10b in SSc [33]. Out of five selected miRNAs, the same expression pattern between miRNA‐seq and qPCR analysis was confirmed only in miRNA‐26a‐2‐3p and miRNA‐485‐3p.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with the presence of antifibrotic factors in SSc-ASC, such as HGF, TIMP-1, and MMP-2, we found that these cells reduced αSMA expression levels and collagen content in DF from SSc patients, demonstrating significant antifibrotic paracrine effects in vitro. These results appear to contrast with recent studies of miRs in silico, which reported a pro-fibrotic ASC signature from SSC patients [23]. Sera from SSc patients have also been shown to favor differentiation of healthy ASC into profibrotic myofibroblast-like cells in vitro [43].…”
Section: Discussioncontrasting
confidence: 82%
“…Although most of these studies have focused on bone-marrow-derived MSC, ASC-based therapies are also controversial. Recent reports of altered molecular signatures in ASC from SSc patients have suggested compromise of their angiogenic and ant-fibrotic activity [23,24,25]; however, few functional studies have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…New advances for EndMT mediators are represented by miRs. These molecules are small non‐coding RNAs, which are post‐transcriptional repressors of genes [121,122]. Previous studies have shown the involvement of several miRs (miR‐29s, miR‐125b and 126, miR‐130) in the development of EndMT [42] and the interaction between TGF‐β and several miRs (miR‐21, miR‐31, miR‐155) in modulating EndMT [42].…”
Section: Mediators Involved In Endmtmentioning
confidence: 99%